Pengaruh Media Pendingin Oli Bekas Pada Proses Quenching Terhadap Kekerasan Linggis Brongsong - Hanggara, Gandi; Putri, Fenoria; Gunawan, Indra (MACHINERY Jurnal Teknologi Terapan, 2022)
The purpose of this study was to determine the effect of the quenching process that uses used oil as a cooling medium with temperature variations of 750oC, 850oC, and 900oC with a holding time of 30 and 40 minutes to the hardness of the eye of the brongsong crowbar which is often subjected to dullness. The main material used by the people of Sukadana village in making this brongsong crowbar is pipa carbon steel ASTM A106 grade B. This pipe belongs to medium carbon steel because it has a carbon element of 0.30%. After the heat treatment process of the brongsong crowbar specimen, hardness testing was carried out using a rockwell hardness test tool. The results of the hardness test were analyzed using ANOVA calculations. From the results of this study, it was found that the brongsong crowbar specimen experienced an increase in hardness, with the highest hardness value of 52.6 HRC obtained from the quenching process using used oil as a cooling medium and with a holding time of 40 minutes at a temperature of 850oC, while the lowest hardness value is obtained from the results of the quenching process using used oil cooling media with a holding time of 30 minutes at a temperature of 750oC of 38.8 HRC. So that it can be known that the highest hardness value is obtained from the results of the quenching process using used oil cooling media with a holding time of 40 minutes at a temperature of 850oC.